1963
DOI: 10.1111/j.1939-0025.1963.tb01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of mental and emotional disorders: A conceptual framework and action possibilities.

Abstract: Prevention is seen as a magic word that has had little action implementation in the field of mental and emotional disorders. Moreover, lay and professional groups appear to have a desultory defeatist attitude toward such activity. In part, this is the result of an inability to conceptualize a usable and meaningful theoretical structure from which research and demonstration programs can be developed. A conceptualization of primary prevention and programs of research and demonstration are presented and discussed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1964
1964
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Primary prevention of psychopathology is a relatively new idea (cf. Bower, 1965Bower, , 1969Caplan, 1961Caplan, , 1964Kessler & Albee, 1975;Zax & Cowen, 1969) which currently arouses as much fervent support (Albee, 1982;Bloom, 1979Bloom, , 1981Bower, 1972;Cowen, 1980;Kelly, 1977) as opposition (Cain, 1967;Cumming, 1972;Henderson, 1975;Lamb, 1981;Lamb & Zusman, 1979;Panzetta, 1971). The major problem is that the concepts of primary prevention which were initially presented with such great promise have led to so few adequately evaluated prevention projects that critics and skeptics abound.…”
Section: Primary Prevention: Evidence For Its Effectiveness With Chilmentioning
confidence: 99%
“…Primary prevention of psychopathology is a relatively new idea (cf. Bower, 1965Bower, , 1969Caplan, 1961Caplan, , 1964Kessler & Albee, 1975;Zax & Cowen, 1969) which currently arouses as much fervent support (Albee, 1982;Bloom, 1979Bloom, , 1981Bower, 1972;Cowen, 1980;Kelly, 1977) as opposition (Cain, 1967;Cumming, 1972;Henderson, 1975;Lamb, 1981;Lamb & Zusman, 1979;Panzetta, 1971). The major problem is that the concepts of primary prevention which were initially presented with such great promise have led to so few adequately evaluated prevention projects that critics and skeptics abound.…”
Section: Primary Prevention: Evidence For Its Effectiveness With Chilmentioning
confidence: 99%
“…The man from Mars or Venus would view with some astonishment the way we march our youth off to the campuses each September, run them through assembly lines of registration with much confusion, and proceed to drill them in intellectual exercises which often seem to them alienated from their present interests and future pursuits. Bower (1963), who was a consultant on school mental health with the National Institute of Mental Health, wrote of the apparent need of our society through its schools to classify some individuals as failures in order to preserve the feeling of superior accomplishment for others. Thus our colleges maintain a constant pressure on the student by means of holding over his head the threat that he will be labeled a failure in the competitive race for the diploma.…”
mentioning
confidence: 99%
“…Psychotogical approaches focus on internal mediating structures and processes (perceptions, feelings, constructs) which individuals develop about their communities. It is suggested that community psychologists make use of and integrate these two research approaches in order to design maximally effective intervention programs.The concept of "primary prevention" (Bower, 1963;Caplan, 1964;Cowen, Gardner, & Zax, 1967) as it relates to community psychology represents a radical shift away from attention to individuals in psychological distress. It involves an orientation to the entire matrix of social, economic, political, biological, cultural, and physical as well as psychological factors which affect human development and growth.…”
mentioning
confidence: 99%
“…The concept of "primary prevention" (Bower, 1963;Caplan, 1964;Cowen, Gardner, & Zax, 1967) as it relates to community psychology represents a radical shift away from attention to individuals in psychological distress. It involves an orientation to the entire matrix of social, economic, political, biological, cultural, and physical as well as psychological factors which affect human development and growth.…”
mentioning
confidence: 99%